New Characterizations for the Essential Norms of Generalized Weighted Composition Operators between Zygmund-Type Spaces - Mostafa Hassanlou; Amir H. Sanatpour (Abstract and Applied Analysis)
We give different types of new characterizations for the boundedness and essential norms of generalized weighted composition operators between Zygmund-type spaces. Consequently, we obtain new characterizations for the compactness of such operators.